Anemia as a risk factor of postpartum hemorrhage at dr. R. Soedjono Hospital, Selong, East Lombok - Ernawati; Komang Ayu Kartika Sari; Nyoman Gede Budiana; Luh Seri Ani (Universitas Udayana, 2018)
Background and purpose: Globally, maternal mortality rate due to labor complications remains high, with postpartum hemorrhage as the most common cause. Studies on the risk factors of postpartum hemorrhage have been widely published, however, its association with maternal anemia is inconsistent. This study aims to explore anemia as a risk factor for postpartum hemorrhage. Methods: A case control study was carried out with 69 women who experienced postpartum hemorrhage as cases and 207 women who had given birth but did not experience hemorrhage as controls. Cases and controls were taken from medical records at the dr. R. Soedjono Hospital, Selong, East Lombok District, West Nusa Tenggara. Cases were selected by systematic random sampling from 147 mothers who experienced postpartum hemorrhage during 2017. Controls were selected in the same way from 2,855 mothers who did not experience postpartum hemorrhage. Cases and controls were matched for birth weight of infants and maternal employment. Data were obtained by medical record extraction in May 2018 consisting of information on hemoglobin concentration, parity, age at pregnancy, birthing method, gestational age, birth spacing and length of labor. Data analysis was performed using logistic regression to determine the adjusted odds ratio (AOR) of anemia. Results: Characteristics of cases and controls were found to be similar in terms of infant birth weight, maternal occupation, parity, gestational age and length of delivery but statistically different by maternal age at pregnancy and birth spacing. Analysis with logistic regression showed that anemia during pregnancy with hemoglobin concentration ≤10 gr/dL was a significant risk factor for postpartum hemorrhage with AOR=16.32 (95%CI: 7.69-34.64). Delivery through caesarean section (SC) or oxytocin drip was also found to significantly reduce the risk of postpartum hemorrhage (AOR=0.03; 95%CI: 0.01-0.13). Conclusion: Anemia during pregnancy with hemoglobin concentration ≤10 gr/dL was found to be a risk factor for postpartum hemorrhage. Prevention and control of anemia in pregnant women need to be enhanced to prevent postpartum hemorrhage.